AUTOPSI FORENSIK DALAM PEMBUKTIAN TINDAK PIDANA PEMBUNUHAN - Novianti Dasma Putri (PT. Hasba Edukasi Mandiri, 2026)
Forensic autopsy is an important instrument in proving the crime of murder, particularly in revealing the cause, manner, and time of the victim's death. In Indonesian criminal justice practice, forensic autopsy is often the basis for the preparation of a visum et repertum, which serves as documentary evidence and/or expert testimony. However, its implementation and utilization still face various legal issues, such as rejection by the victim's family, differing interpretations by law enforcement officials, and the suboptimal normative regulations in the Criminal Procedure Code (KUHAP). This study aims to analyze the position and evidentiary power of forensic autopsy in murder cases and examine its regulations from a criminal procedure law perspective. The research method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that forensic autopsy plays a strategic role in proving the elements of the crime of murder, particularly regarding the causal relationship between the perpetrator's actions and the victim's death. However, the absence of clear and comprehensive regulations regarding forensic autopsy in the Criminal Procedure Code (KUHAP) creates legal uncertainty in practice. Therefore, strengthening and harmonizing forensic autopsy regulations is needed to ensure legal certainty, justice, and the effectiveness of evidence in murder cases.